Methodical approach to assessing the level of environmental safety of agricultural land use - Kupriianchyk, I. (Land Management, Cadastre and Land Monitoring, 2022)
The article stipulates that in the course of agricultural activity land resources are, first of all, the property of nature, at the same time forming the internal component of the production process, as well as its generalizing aspects. In view of this, land resources are the main means of production in the agricultural sector and the physical basis for agricultural production, as well as an element of natural productive forces. The issues of assessing the level of ecological safety of agricultural land use are highlighted and a methodological approach is proposed, based on a comprehensive analysis of a set of criteria and indicators that most fully characterize environmental risks and threats to land use, taking into account the assimilation potential of agroecosystems. The proposed method of assessing the environmental safety of agricultural land use by ranking regions of the country by integrated index or individual criteria (indicators) allows to classify them by levels of land quality, degradation, anthropogenic impact and eco-destructive load on land. This will identify regions most vulnerable to adverse environmental impacts, which will primarily need assistance and prevention and elimination of environmental threats and risks in order to implement long-term and short-term plans for environmentally friendly agricultural land use at both state and local levels. Key words: sustainable development, ecological sustainability, agricultural land use